Behind OPEC’s Invitation for Indonesia to Rejoin: An Analysis of Membership Dynamics in an International Organization - Novita Putri Rudiany; Indra Kusumawardhana (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
The membership structure matters to ensure a durable negotiating forum in an international organization. However, in July 2017, Saudi Arabia and the United Arab Emirates, on behalf of the Organization of the Petroleum Exporting Countries (OPEC), requested Indonesia to reactivate its membership, which the country had suspended—for the second time—in November 2016. The first suspension was in January 2009—annulled in January 2016. The Government of Indonesia (GoI) then welcomed the invitation. This study aims to analyze OPEC’s membership scheme, which has given leeway to its members to send a request like the above. In-depth interviews were conducted with Indonesia’s representatives in OPEC to capture the organization’s internal condition. By analyzing the organization’s membership dynamics, we can identify three reasons behind Indonesia’s invitation to rejoin. The first is because OPEC’s country members need Indonesia’s presence in negotiations as they consider Indonesia neutral. Second, OPEC needs a country with a different attribute to strengthen the organization’s image of diversity on the international stage. The third reason is the historical elements. OPEC strives to maintain historically good relations with the GoI as the country has contributed to the organization’s development. For those reasons, an international organization might reinvite its former member to join the group.